ENHANCING IOT SYSTEMS WITH SCALABLE CLOUD ARCHITECTURES FOR REAL-TIME DATA PROCESSING - Sai Srujan Siripuram (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY, 2024)
The development and application of Internet of Things (IoT) systems coupled with scalable cloud architectures for real-time data processing are examined in detail in this extensive essay. From data ingestion to security concerns, the paper explores the basic difficulties enterprises face while overseeing extensive IoT deployments. It explores the elements of cloud-based architecture, highlighting the crucial roles played by processing frameworks, storage options, and data intake levels. The essay discusses edge analytics integration and emphasizes how it can improve privacy, optimize bandwidth, and reduce latency. Important scalability issues in both horizontal and vertical dimensions are also covered in the article, along with implementation best practices, including microservices architecture and thorough monitoring techniques. Additionally, it looks at the security environment of IoT cloud infrastructures, including compliance frameworks, data protection strategies, and device security.